Answer:
-6x² + 2x - 4
Explanation:
![(12x^3 - 4x^2 + 8x)/(-2x)](https://img.qammunity.org/2019/formulas/mathematics/high-school/jvsvjt2noqr4urc8ou7is2482xiuj3pamu.png)
Step 1:
First, group the integers together and divide those:
= -6
= 2 (since 4 is also a negative number, you will turn the (-) sign into a (+) sign given the rule that two negatives = a positive.)
= -4
Step 2:
Next, group the variables and divide those (when in division, you will subtract the exponents instead of dividing):
= x²
= x (when there is only a variable and no exponent, you can assume 1 as it's exponent.)
=
= 0
Step 3:
Combine the integers and variables in the order given and you will get:
-6x² + 2x - 4